Impact of Temperature Stresses on Wheat Quality: A Focus on Starch and Protein Composition - Pei Han; Yaping Wang; Hui Sun (Foods, 2025)
With climate change, maintaining wheat quality has become essential for the functional properties, end-use, commodity value, and nutritional benefits of wheat flour. Temperature indirectly influences wheat quality by modulating grain size, starch and protein content, and the balance between these components. This review systematically analyzes temperature-mediated alterations in wheat grain quality, with particular emphasis on the two core components: starch and protein. Specifically, daytime warming generally increases protein content while reducing starch accumulation; however, temperatures exceeding 30 °C diminish key protein quality parameters (UPP%, Glu/Gli ratio, HMW-GS/LMW-GS ratio). Nighttime warming enhances protein quality but compromises starch content and yield potential. Conversely, under low-temperature conditions, starch content declines, whereas protein content is primarily influenced by genotypes and treated temperatures. Furthermore, the underlying mechanisms driving temperature-induced changes in wheat quality traits are discussed. However, the mechanisms of temperature effects have not been fully elucidated, and the results often vary between regions or over years. Thus, identifying conserved high/low-temperature resistance genes, QTLs, epialleles, and epiQTL, as well as developing corresponding molecular markers and epi-markers, is an urgent priority. Meanwhile, genome-editing tools such as CRISPR/Cas could serve as a powerful approach for creating new wheat germplasm with durable high/low-temperature resistance.